Fatty acid composition, cholesterol content and lipid oxidation indices of intramuscular fat from skeletal muscles of beaver (Castor fiber L.). (April 2019) - Domaradzki, Piotr; Florek, Mariusz; Skałecki, Piotr; Litwińczuk, Anna; Kędzierska-Matysek, Monika; Wolanciuk, Anna; Tajchman, Katarzyna
Abstract: The lipid characteristics of the intramuscular fat (IMF) from skeletal muscles of different beaver carcass parts (the loin, hind leg and shoulder) were characterised in detail for the first time. The shoulder muscles had higher ( P  < 0.05) proportion of n -3 polyunsaturated fatty acids (PUFA) than the loin muscles, which had higher percentages of saturated fatty acids (SFA), odd-chain fatty acids (OCFA) and sum of conjugated linoleic acids (ΣCLA). Moreover, the shoulder muscles were found to contain higher fat, cholesterol and total fatty acids (FA) concentrations, as well had a beneficial fatty acid profile, especially in terms of the absolute content of PUFA and some nutritional FA indices (thrombogenic index and SFA/PUFA), as well as FA ratios ( n -6/ n -3 and PUFA/SFA). No differences ( P  > 0.05) in lipid oxidation parameters (FFA, PV and TBARS) were observed between muscles from different carcass parts. Irrespective of muscle location, the predominant class of FA in IMF of beaver was PUFA (averaging 49.39%), followed by SFA (27.81%) and MUFA cis (15.96%). Linoleic acid (LA, 18:2 n-6) was the most abundant FA in all muscles (>34% of total FA). Minor percentages of unusual FA (OCFA, trans FA and branched-chain FA), which are more typical for ruminants than monogastric animals, were also detected (3.46%, 1.92% and 1.22%, respectively). Highlights: Lipid characteristics in intramuscular fat (IMF) from selected skeletal muscles of beaver were analysed. The predominant class of FA in the beaver IMF was PUFA (averaging 49.39%). Linoleic acid (LA, 18:2 n -6) was the most abundant FA in all skeletal muscles (averaging 36.90%). The shoulder muscles had a beneficial FA profile compared to muscles from loin and hind leg. Several unusual FA such as odd-, branched-chain FA, trans FA and CLAs were detected.